Use and need of dental prosthesis among community dwelling elderly: a cross-sectional population-based study - Damieli Peron; Francisco Wilker Mustafa Gomes Muniz; Jaqueline Colaço; Milena Giotti Marostega; Jéssica Jardim Dias; Cassiano Kuchenbecker Rösing; Paulo Roberto Grafitti Colussi (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2022)
Abstract Background By the use of complete or partial dental prosthesis, function, esthetics, and phonetics are reestablished. Few population-based studies are available in the literature using an older adult population. Objective Evaluate the use of and need for dental prostheses and their associated factors. Method This study included a random sample of 287 elderly, in the city of Cruz Alta, Brazil. Use of and need for dental prostheses were the main outcomes, and two analytical models were constructed. Subgroup analyses were performed for individuals using fixed partial denture (FPD) and removable (partial and/or complete) dental prosthesis (RDP). Results Use of and need for dental prosthesis were identified in 83.6% (n=240) and 42.5% (n=122) of the elderly, respectively. Women presented a significantly higher prevalence ratio (PR) for use of dental prostheses (PR=1.15; 95%IC:1.02-1.28) and lower need (PR=0.70; 95%IC:0.54-0.91). No statistically significant difference was demonstrated for the use of FPD regarding the sex. Higher education level was associated with lower use of prostheses (PR=0.73; 95%IC:0.58-0.91) when compared to lower level of education. Medium level of education showed a significantly lower need for dental prostheses (PR=0.61 - 95%IC:0.39-0.94). Those that did not consume alcohol presented with a significantly lower use of FPD and RDP (PR=0.46; 95%IC:0.23-0.93 and 0.90;0.81-0.99, respectively). Conclusion The use of and need for dental prostheses were associated with sex, level of education, and behavioral factors.